2007
DOI: 10.1111/j.1365-2443.2007.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the p400/mDomino chromatin‐remodeling ATPase in embryonic hematopoiesis

Abstract: The SWI2/SNF2 family ATPase, p400/mDomino, is a core subunit of a large chromatin-remodeling complex, and is currently suggested to play a unique function in histone variant exchange, a process by which chromatin structure is altered. Here, we investigated the role of p400/mDomino in mammalian development by generating mutant mice with a targeted deletion of the N-terminal domain of p400/mDomino (referred to as mDom). The mDom∆N mice died on embryonic day 11.5 (E11.5), and displayed an anemic appearance and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…However, a recent study showed that the siRNA-mediated knockdown of p400/mDomino in mouse cells reduces the proliferation rate of embryonic stem cells without p21 up-regulation, and has only a modest effect on the cell cycle of embryonic fibroblasts (23). This discrepancy in the effect of p400 knockdown on cellular proliferation could be attributable to cell-type-specific roles of p400/mDomino, or different levels of residual p400/mDomino protein might have resulted in the distinct phenotypes in these knockdown experiments.We previously reported that mice with an N-terminally deleted p400/mDomino mutation die in utero with a defect in primitive erythropoiesis, indicating that the mDomino complex is essential for early development (24). In this study, we …”
mentioning
confidence: 69%
See 3 more Smart Citations
“…However, a recent study showed that the siRNA-mediated knockdown of p400/mDomino in mouse cells reduces the proliferation rate of embryonic stem cells without p21 up-regulation, and has only a modest effect on the cell cycle of embryonic fibroblasts (23). This discrepancy in the effect of p400 knockdown on cellular proliferation could be attributable to cell-type-specific roles of p400/mDomino, or different levels of residual p400/mDomino protein might have resulted in the distinct phenotypes in these knockdown experiments.We previously reported that mice with an N-terminally deleted p400/mDomino mutation die in utero with a defect in primitive erythropoiesis, indicating that the mDomino complex is essential for early development (24). In this study, we …”
mentioning
confidence: 69%
“…1D). We have not determined whether mDom ⌬/⌬ embryos die in a very early stage of embryogenesis, or can develop at least to embryonic day 8.5 as observed in the homozygous embryos expressing the N-terminally deleted mDomino mutant (24).…”
Section: Generation Of P400/mdomino Conditional Knock-out Mice-mentioning
confidence: 99%
See 2 more Smart Citations
“…Homozygous knockout mice died on embryonic day 11.5 (E11.5), and displayed an anemic appearance and slight deformity of the neural tube. Their results suggest that p400/mDomino plays a critical role in embryonic hematopoiesis by regulating the expression of developmentally essential genes such as those in the Hox gene cluster (Ueda et al, 2007). Tip60-p400 is necessary to maintain characteristic features of Embryonic Stem Cells (ESCs) (Fazzio et al, 2008).…”
Section: Hdomino P400/eaf1/swr1mentioning
confidence: 99%